Prevalence of red panda amdoparvovirus infection in European zoos - Kuhar, Urška; Tomášek, Oldřich; Sós, Endre; Mede, Jana; Kastelic, Marjan; Jež, Nuša; Petrikova, Michaela; Jensen, Trine Hammer; Alex, Charles Everett; Jamnikar-Ciglenecki, Urška; Kvapil, Pavel (Frontiers in Veterinary Science, 2023)
Red panda amdoparvovirus (RPAV) was first described in captive red pandas (Ailurus fulgens) at a zoo in the United States in 2018. Subsequently, the prevalence of infection in zoos in the United States was reported to be 50%; however, RPAV prevalence outside the United States remains unstudied. This study was conducted to investigate the prevalence of RPAV in 134 red pandas from zoos in Europe. Overall, RPAV was detected with PCR in 21 of 62 zoos (33.9%), and the virus prevalence among individuals was estimated to be 24.2% (95% confidence interval: 17.4%-32.0%). Remarkably, adult females tested positive for RPAV more frequently than adult males. Zoos where RPAV was detected reported a significantly higher occurrence of alopecia (and clinical signs in general), whereas other This is a provisional file, not the final typeset article commonly reported problems (fecal disorders and dental disease) showed no difference. A repeated pooled sampling of two positive individuals further showed that RPAV excretion in feces is intermittent, with the viral DNA being only detected on 8 out of 14 sampling days. The intermittent nature of excretion implies that RPAV prevalence may be higher than the estimated value.